EFEKTIVITAS PENGGUNAAN JALUR LAMBAT PADA RUAS JALAN DR. LUKMONOHADI DAN DR. RAMELAN KUDUS DI KABUPATEN KUDUS - Kholil, Munawar; Fauzan, Nur Maulana; Rizani, Mohammad Debby; Yudaningrum, Farida (Universitas PGRI Semarang, 2023)
Kudus street is a national road that connects Jakarta-Semarang-Surabaya-Banyuwangi, on this north coast road as the need for mobility of goods delivery or mobility of residents between cities. On the way Dr. Lukmonohadi – Dr. Ramelan has a slow lane on the left side of the road. The purpose of the existence of the slow lane on road DR. Lukmonohadi-Dr. Ramelan is to smooth traffic and reduce the fatality rate of accidents in the fast lane, but due to very high shopping and industrial activities that can interfere with performance on these roads. The purpose of this research study is to review the effectiveness of the slow lane on the Dr. Lukmonohadi-Dr. The Ramelan is working properly or not. From the results of the analysis of traffic performance measured using the degree of saturation (DS) for Road Dr. Lukmonohadi of 0.57, while Road Dr. Ramelan is 0.61. From the level of congestion that can be obtained from the value of the side barriers that Dr. Lukmonohadi until Dr. Ramelan is included in the medium side resistance class (M). Based on the comparison of the accident rate from 2016-2021 the number of accidents continues to increase. The recommended recommendations are that it is necessary to repair and add road facilities such as repair of separator paint, faded road markings, addition of zebra crossings in pedestrian-congested locations and asphalt repairs on slow lanes because there is a lot of asphalt that is peeling and has holes, it is very dangerous for road users crossing it. Based on the results of the analysis for the slow lane, it can be concluded that the slow lane has been effective in facilitating traffic flow to reduce the number of accidents on the fast lane.